Analisis Slump dengan Penambahan Serat Eceng Gondok (1%,2%, 4%) - Wizdan Adani; Mitsaq Addina Nisa (GLOBAL SCIENTS PUBLISHER, 2026)
The mechanical characteristics of concrete—which is strong in compression but weak in tension—pose a major obstacle to structural ductility. The use of natural water hyacinth (Eichhornia crassipes) fibers as a waste product offers an ecological solution to reduce the use of expensive and environmentally unfriendly synthetic fibers. This study aims to analyze the effects of adding water hyacinth fibers on the mechanical properties of concrete, to compare its compressive and flexural strength with that of ordinary concrete, and to determine the optimal fiber content. The research method involved laboratory experiments using fiber content variations of 0%, 1%, 2%, and 4% of the cement weight, with uniform fiber lengths of 3 cm that had been soaked in a NaOH solution for 8 hours and supplemented with a superplasticizer. The parameters tested included the slump value and the density of fresh concrete, the compressive strength of cylindrical specimens at 7, 14, and 28 days, and the flexural tensile strength of beams at 14 and 28 days. The fresh concrete test results showed that the slump value was directly proportional to the fiber content, ranging from 14 cm (0%) to 16 cm (4%) due to the effect of the superplasticizer. In the mechanical property tests of 28-day-old hardened concrete, the average compressive strength decreased as the fiber content increased, namely 27.01 MPa (0%), 16.83 MPa (1%), 9.88 MPa (2%), and 8.11 MPa (4%). This decrease is due to the tendency of organic fibers to clump together, resulting in a less homogeneous concrete mixture. Conversely, the 28-day flexural strength test showed an increase in the initial variations before eventually dropping sharply, with average values of 1.27 MPa (0%) and 1.31 MPa (1%), reaching an optimal point at the 2% variation of 1.37 MPa, and dropping to 1.03 MPa at the 4% variation. Based on the evaluation, the addition of water hyacinth fiber effectively improves the flexural strength of concrete within an optimal variation range of 2%, but has a negative impact on its compressive strength.